2018
DOI: 10.1515/intag-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic dehydration of Braeburn variety apples in the production of sustainable food products

Abstract: A b s t r a c t. The aim of this work was to investigate the effects of osmotic dehydration conditions on the properties of osmotically pre-treated dried apples. The scope of research included analysing the most important mass exchange coefficients, i.e. water loss, solid gain, reduced water content and water activity, as well as colour changes of the obtained dried product. In the study, apples were osmotically dehydrated in one of two 60% solutions: sucrose or sucrose with an addition of chokeberry juice con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The influence of temperature on OD was confirmed by Ciurzyńska et al . [ 30 ], in the OD of apples at temperatures of 40 °C and 60 °C. In this experiment, xylitol was determined as the most effective osmotic reagent ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of temperature on OD was confirmed by Ciurzyńska et al . [ 30 ], in the OD of apples at temperatures of 40 °C and 60 °C. In this experiment, xylitol was determined as the most effective osmotic reagent ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, facilitating the outflow of water. Mundada et al [25] and Ciurzyńska et al [29] also reported that with an increase in temperature of an osmotic solution increased the water loss and solute gain of different fruit samples. Consequently, the moisture content of the sample decreased, and • Brix content of the sample increased at a higher concentration of the osmotic solutions and temperature as well.…”
Section: Water Loss and Solute Gain Of Papayamentioning
confidence: 95%
“…The achieved values were classified into one homogenous group. According to Ciurzyńska et al [35], an osmotic solution type and temperature have significant effect on the color of apple tissue. An increase values of a* parameter was also observed in the case of maltitol.…”
Section: Color Changesmentioning
confidence: 99%